The bishop's daughter - Johns, Patricia (Romance writer) (Zebra historical romance., 2019)
As a bishop<U+2019>s daughter and good Amish mother, widowed Sadie Hochstetler teaches her young son that God blesses those who try their best to please Him. But her brief marriage taught her that life is infinitely more complicated than that. Older, and serious, her late husband seemed a sensible choice<U+2014>especially compared to Elijah Fisher, the spirited boy with whom she butted heads and hearts. Then Elijah abruptly left for the Englisher world, taking Sadie<U+2019>s beloved brother along with him<U+2014>a double betrayal she still strives to forgive. Especially now that Elijah has returned . . . Elijah plans to stay in the Amish community only as long as he<U+2019>s needed, helping his family and working for Sadie<U+2019>s ailing father. The outside world has changed him, leading him to question rules and restrictions that others take on faith. Once, he<U+2019>d been head over heels in love with the bishop<U+2019>s daughter<U+2014>a girl he was judged unworthy of courting. Nine years have changed so much between them. Yet something remains<U+2014>a spark that, for all their differences, might light the way home again . . .